INFLUENCE OF Beauveria bassiana INFECTION ON RESPIRATORY AND REPRODUCTIVE PARAMETERS OF SILKWORM Bombyx mori L - BEGUM, SYEDA FAKRUNNISA; SAVITHRI, G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The mulberry silkworm, Bombyx mori is highly susceptible to diseases caused by viruses, bacteria, fungi and protozoa. The most virulent and contagious disease is muscardine, which is caused by Beauveria bassiana. The present study is focused to understand the modulations in the oxygen consumption, fecundity, hatching percentage, unfertile eggs and dead egg percentage of silkworms i.e., in bivoltine double hybrid (CSR 2 X CSR 27 and CSR6 X CSR26) infected with Beauveria bassiana. The daily oxygen consumption of healthy batch showed a steady increase in the oxygen consumption from first day (0.615 ml of O2/hr/gm wet weight) to fifth day (0.827 ml of O2/hr/gm wet weight) in the control batch. It is higher on the second day (0.671 ml of O2/hr/gm wet weight) in the infected batch with gradual decline till the sixth day of the fifth instar (0.598 ml of O2/hr/gm wet weight) compared to healthy silkworms. Significant reduction in the number of eggs (595) and hatching percentage (75.8%) was recorded in inoculated silk moths compared to number of eggs laid (695) and hatching percentage (99.1%) in control. Significantly high percentage of unfertilized eggs (16.8%) and dead egg percentage (4.37%) was noticed in the experimental animals compared to unfertilized egg percentage (0.14%) and dead egg percentage (0.72%) in control. So, it is necessary to prevent the disease occurrence, especially during silkworm seed rearing to obtain quality commercial silkworm seed necessary for the progress of the industry. Therefore, there is a dire need to carry out research in basic and applied aspects to develop strategies to control the disease.